Do ensino presencial ao ensino a distância: a inovação na prática pedagógica de professores de matemática - Faria, Elisabeth Cristina de (2012)
This study has the principal aim to understand the transition process which a group of teachers who work with Calculus content regarding tutoring and mentoring in distance Mathematics Degree course. The research task aims to understand what components there are in the transition from classroom teaching to distance teaching and what strategies are used by the teachers group in developing their activities. The theoretical framework of this study is based on the Everett M. Rogers Innovation- Decision Process supported by authors who discuss educational innovation, teacher training and distance education. The research, methodologically, relies on content analysis proposed by Laurence Bardin, from which we developed a thematic analysis from the collected material through semi-structured interviews, field observations and document analysis. The research was conducted with four teachers from a Calculus group of Mathematics Degree course which was taught at distance. Linking the analyzed themes and the research it was found that the teachers prior knowledge, though not directly connected to on line education may facilitate the relationship with innovation, it means, the distance acceptance with its specificities. It also positively contributed to the acceptance of innovation, group work, because it is made up of members who had already developed similar academic experiences it was facilitated. Beliefs and expectations are elements that also raise by using the innovation, verifying that teachers, at their own time, develop a special relationship with the innovation and at the same time, the group develops a collective relationship making easier to overcome some fears toward the novelty. The main contribution of this research is to understand the relationships that teachers establish throughout the work doing the didactic transposition from a classroom course to distance course. To understand how teachers deal with innovative situations teaching in practice may represent a significant contribution to teachers training to work with distance teaching way